Policy in a Time of Fear: Blinded by Safety and Security - van Es, Annemieke (Pécs journal of international and European law, 2016)
After the attacks on New York, Madrid and London, various types of legislation have been implemented to combat and prevent terrorism. Although such measures are necessary to protect society, it is also essential that criminal legislation especially is limited by the boundaries set by the values in a democratic society. When those lines are crossed, legal protection can’t be guaranteed. The proposal to criminalize the glorification of terrorist acts is criticized in accordance with the freedom of expression (ECHR Art. 10).